Desenvolvimento de procedimentos em fluxo envolvendo espectrofotometria convencional e com longo caminho óptico para determinação de ânions em águas - Bonifacio, Viviane Gomes (2008)
In this work, five procedures were developed for determination of anions (chloride, sulphate, phosphate and fluoride), with spectrophotometric detection, being four employing a 100-cm optical length flow-cell and one of them employing a cell whith 1 cm optical length. The first procedure employing flow injection analysis with long pathlenght for chloride determination in natural waters was based in the spectrophotometric procedure described in Standard Methods130 in which the reaction between mercury(II) thiocianate and chloride displace the thiocianate ions yielding a reddish complex with iron(III), that was spectrophotometrically monitored at 455 nm. The analytical curve obtained was linear in the chloride concentration range of 1.0 to 50 mg L-1 (r = 0.9989) with a detection limit of 0.2 mg L-1 (3óblank / slope) and a quantification limit of 0.7 mg L-1 (10óblank / slope), RSD < 1.0% (n = 20) and a sampling rate of 72 h-1. The second procedure for chloride determination employed a solid-phase reactor containing silver chloranilate immobilized coupled to the FIA system. The chloride determination is based on the reaction between chloride and silver chloranilate yielding silver chloride, displacing chloranilate ions which were spectrophotometrically detected at 530 nm and the absorbance signals proportional to the chloride concentration. The analytical curve showed a good linearity in the chloride concentration range of 0.5 to 100 mg L-1 (r = 0.9997) with a detection limit of 0.3 mg L-1 (3óblank / slope) and a quantification limit of 0.5 mg L-1 (10óblank / slope), RSD of 1.05% (n = 20) and a sampling rate of 80 h-1. The flow procedure for sulphate determination in natural waters employed a solid-phase reactor containing barium chloranilate immobilized. The determination is based on the reaction between sulphate ions and barium chloranilate yielding barium sulphate, displacing the chloranilate ions that were spectrophotometrically detected at 530 nm. The analytical curve obtained was linear in the sulphate concentration range of 2.5 to 40 mg L-1 ( r = 0.9994) a detection limit of 0.1 mg L-1 (3óblank / slope) and a quantification limit of 0.3 mg L-1 (10óblank / slope), RSD < 1.0% (n = 10) and a sampling rate of 50 h-1. The proposed procedure for phosphate determination in natural waters employing flow injection analysis with long pathlenght spectrophotometry is based on the colorless reaction of iron(III) thiocianate and phosphate ions. Iron(III) reacts with thiocianate yielding FeSCN2+, a reddish complex with maximum absorbance in 468 nm. The phosphate ions in contact with FeSCN2+ yield a colorless complex between iron(III) and phosphate, with non-defined stoichiometry. The decrease of the absorbance signals is proportional to the phosphate concentration in the samples. The analytical curve obtained was linear in the phosphate concentration range of 10 to 100 µg L-1 (r = 0.9996) a detection limit of 4.5 µg L-1 (3óblank / slope) and a quantification limit of 15.6 µg L-1 (10óblank / slope), RSD < 1.0% (n = 10) and a sampling rate of 55 h-1. The procedure for fluoride determination in mineral waters employing a 1-cm optical flow-cell was based on the same procedure for phosphate determination. The reaction between fluoride ions and FeSCN2+ yield the colorless FeF6 3-complex causing an absorbance decrease, proportional to the fluoride concentration in the samples. The analytical curve showed a good linearity for the fluoride concentration range of 0.02 to 5.33 mg L-1 (r = 0.9997) with a detection limit of 5.3 µg L-1 (3óblank / slope) and a quantification limit of 17.6 µg L-1 (10óblank / slope), RSD of 1.9% (n = 20) and a sampling rate of 110 h-1. Results obtained with the proposed procedures were compared with those obtained with the official methods from Standard Methods showing a good agreement at the 95% confidence level.